2019
DOI: 10.1039/c9pp00040b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of palmatine hydrochloride mediated photodynamic therapy on oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a common malignant tumor, accounting for about 7% of all malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Palmatine has been reported to have anticancer effects in CRC, HCC, pancreatic cancer, oral squamous cell carcinoma, breast cancer, ovarian cancer, and prostate cancer both in vitro and in vivo ( Long et al, 2019 ; Qi et al, 2019 ). It induces antiproliferative effects, anti-inflammatory effects, G 2 /M phase arrest, and cell apoptosis via mitochondrial pathways by targeting cytokines and aurora kinase A (AURKA) in CRC cells ( Ma et al, 2016 ; Liu et al, 2020e ).…”
Section: Antitumor Effects and Corresponding Mechanismsmentioning
confidence: 99%
“…Palmatine has been reported to have anticancer effects in CRC, HCC, pancreatic cancer, oral squamous cell carcinoma, breast cancer, ovarian cancer, and prostate cancer both in vitro and in vivo ( Long et al, 2019 ; Qi et al, 2019 ). It induces antiproliferative effects, anti-inflammatory effects, G 2 /M phase arrest, and cell apoptosis via mitochondrial pathways by targeting cytokines and aurora kinase A (AURKA) in CRC cells ( Ma et al, 2016 ; Liu et al, 2020e ).…”
Section: Antitumor Effects and Corresponding Mechanismsmentioning
confidence: 99%
“…Evidence from our previous investigation showed that palmatine could protect against triple negative mammary carcinoma in female balb/c mice which was associated with the activation of the endogenous tumor suppressor gene p53 ( Ativui et al, 2021 ). In vitro experiments have also demonstrated the efficacy of palmatine against tumor migration and invasion ( Hambright et al, 2015 ; Qi et al, 2019 ). This research was conducted to validate the efficacy of palmatine in protecting breast cancer metastasis in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The DNA damage generated by a combination of berberine with UVA irradiation induced a significant blockage of EAC cells (Ehrlich ascites carcinoma) in the S and G2/M phases and the decrease of cell proliferation after 24 h of treatment [ 25 ]. Photodynamic therapy of palmatine exhibited a potent phototoxic effect in cell proliferation and produced cell apoptosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%